Genetic Paradoxes in an Italian Family with PARK2 Multiexon Duplication. Issue 6 (8th September 2017) - Petrucci, Simona; Ferrazzano, Gina; Ginevrino, Monia; Tolve, Manuela; Berardelli, Isabella; Berardelli, Alfredo; Fabbrini, Giovanni; Valente, Enza Maria
Abstract : View Supplementary Video1 View Supplementary Video2